2017
DOI: 10.1002/anie.201702409
|View full text |Cite
|
Sign up to set email alerts
|

Base‐Controlled Completely Selective Linear or Branched Rhodium(I)‐Catalyzed C−H ortho‐Alkylation of Azines without Preactivation

Abstract: A [Rh(I)]/bisphosphine/base catalytic system for the ortho-selective C–H alkylation of azines by acrylates and acrylamides is reported. This catalytic system features an unprecedented complete linear or branched selectivity that is solely dependent on the catalytic base that is used. Complete branched selectivity is even achieved for ethyl methacrylate, which enables the introduction of a quaternary carbon center. Excellent functional group compatibility is demonstrated for both linear and branched alkylations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 21 publications
0
32
0
3
Order By: Relevance
“…[15] Ther eaction developed by Chang and coworkers indeed proceeds with high efficiency and complete selectivity for the linear isomers,a lthough the starting Noxides have to be used in excess (2.5 equivalents) to prevent double alkylation, which can be efficiently promoted by reversing the stoichiometry.A san ote,t he deoxygenation of the alkylated N-oxides can be successfully performed in ao ne-pot sequence by treatment of the crude reaction mixtures with PCl 3 .T he same transformation could also be achieved using ac ombination of cationic [Ir(cod) 2 ]BArF as the catalyst and (AE)-BINAP as al igand for the direct alkylation of 2-substituted pyridine N-oxides with excess acrylates. [17] Theuse of potassium pivalate provides the linear products with high selectivity [Scheme 3, Eq. [17] Theuse of potassium pivalate provides the linear products with high selectivity [Scheme 3, Eq.…”
Section: Alkylation With Alkenesmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Ther eaction developed by Chang and coworkers indeed proceeds with high efficiency and complete selectivity for the linear isomers,a lthough the starting Noxides have to be used in excess (2.5 equivalents) to prevent double alkylation, which can be efficiently promoted by reversing the stoichiometry.A san ote,t he deoxygenation of the alkylated N-oxides can be successfully performed in ao ne-pot sequence by treatment of the crude reaction mixtures with PCl 3 .T he same transformation could also be achieved using ac ombination of cationic [Ir(cod) 2 ]BArF as the catalyst and (AE)-BINAP as al igand for the direct alkylation of 2-substituted pyridine N-oxides with excess acrylates. [17] Theuse of potassium pivalate provides the linear products with high selectivity [Scheme 3, Eq. [17] Theuse of potassium pivalate provides the linear products with high selectivity [Scheme 3, Eq.…”
Section: Alkylation With Alkenesmentioning
confidence: 99%
“…[15] Under these conditions,t he linear isomers are obtained selectively in excellent yields.A na symmetric variant was later disclosed by Rovis for the rhodium-catalyzed direct alkylation of benzoxazoles with alarge excess of a-substituted acrylates. I nterestingly,m echanistic studies suggested that migratory insertion or b-hydride elimination is the enantiodetermining step,rather than an enantioselective protonation of ar hodium(I) enolate which is the commonly accepted pathway for related additions of arylboronic acids to methacrylate derivatives.T he use of ab ulky phosphine ligand, CTH-(R)-xylyl-P-Phos is also crucial to reach high levels of reactivity and enantioselectivity.M ore recently,E llman and co-workers extended their work on the linear-v ersus branched-selective rhodium-catalyzed alkylation of heteroarenes (see Section 2.1.1 for the use of pyridine derivatives) [17] to the C2-branched selective alkylation of benzimidazoles by using N,N-dimethylacrylamidea nd ethyl methacrylate as coupling partners [Scheme 30, Eq. (2)].…”
Section: Alkylation With Alkenesmentioning
confidence: 99%
“…In consideration of the unique selectivity switch [16] accomplished with the cobalt(III)-catalyzed C À Ha lkylation, we became intrigued by rationalizing their mode of action. To this end, product equilibration through CÀCactivation [17] was excluded by the exposure of the independently prepared products 3aa and 4aa to the complementary reaction conditions (Scheme 3a).…”
mentioning
confidence: 99%
“…[15] An initial C-H alkylation of quinoline by Rh(I) catalysis [16] provided 8 , which upon reaction with hydrazine gave hydrazide 9 in high yield. Condensation of 9 with imidate 10 afforded alkenyl-substituted triazole 11 .…”
mentioning
confidence: 99%